2021
DOI: 10.3390/rs13081566
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Changes of Vegetation Net Primary Productivity and Its Driving Factors on the Qinghai-Tibetan Plateau from 2001 to 2017

Abstract: The Qinghai-Tibetan Plateau (QTP) is the highest plateau in the world. Under the background of global change, it is of unique significance to study the net primary productivity (NPP) of vegetation on the QTP. Based on the Google Earth Engine (GEE) cloud computing platform, the spatio-temporal variation characteristics of the NPP on the QTP from 2001 to 2017 were studied, and the impacts of climate change, elevation and human activity on the NPP in the QTP were discussed. The mean and trend of NPP over the QTP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 37 publications
3
13
0
Order By: Relevance
“…With the development of 3S technology, the analysis of the driving forces of NPP in different regions and scales has become more extensive [ 50 ]. Temperature, precipitation [ 51 ], net radiation [ 52 ], and human activities [ 53 , 54 ] have all been shown to influence NPP. In particular, grazing as one of the human activities is a major factor for changes in NPP in grassland ecosystems [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the development of 3S technology, the analysis of the driving forces of NPP in different regions and scales has become more extensive [ 50 ]. Temperature, precipitation [ 51 ], net radiation [ 52 ], and human activities [ 53 , 54 ] have all been shown to influence NPP. In particular, grazing as one of the human activities is a major factor for changes in NPP in grassland ecosystems [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Precipitation and temperature are fundamental driving forces for ecosystem process change and vegetation distribution as well as productivity in QTP (Huang et al, 2016;Liu et al, 2021;yin Zhang et al, 2021). To analyze the climatic controls on each ES indicator, spatial multiple regression analysis is a better choice than spatial correlation analysis owing to the former's causal explanatory power.…”
Section: The Influence Factors On the Variations Of Ecosystem Service...mentioning
confidence: 99%
“…However, we found that topographic factors (elevation and slope) and geomorphic type dominated the vegetation growth in the Sanjiang Plain, thus dominating the spatial differentiation of CI. Topographic factors (elevation and slope), which were of great importance in redistributing the solar energy and precipitation [30], generally controlled the soil condition through different processes [66], determining the spatial characteristics of CI. Notably, climatic factors (average annual temperature and annual precipitation) and aspect had the smallest q values, but they still had a notable impact on the spatial differentiation of CI when they interacted with other driving factors.…”
Section: Driving Factors Of the Spatial Distribution Of CImentioning
confidence: 99%
“…Notably, climatic factors (average annual temperature and annual precipitation) and aspect had the smallest q values, but they still had a notable impact on the spatial differentiation of CI when they interacted with other driving factors. Related studies have also shown that the interactions between two driving forces could enhance the impact of a single factor [30,59,66]. Therefore, the government should use the land rationally according to the characteristics of topographic factors (elevation and slope) and geomorphic type in the Sanjiang Plain to improve grain production and ensure regional ecological security.…”
Section: Driving Factors Of the Spatial Distribution Of CImentioning
confidence: 99%